Damage Characteristics of Sandstone Subjected to Coupled Effect of Freezing-Thawing Cycles and Acid Environment. (5th July 2018) - Deng, Hongwei; Yu, Songtao; Deng, Junren
Abstract : In order to figure out the damage characteristics and mechanisms of sandstone under coupled effect of acid erosion and recurrent freezing-thawing cycles, sulfuric acid is chosen as acid solution, and sandstone, representative stone in Sichuan province, is chosen as a sample to conduct the freezing-thawing cycling test. In the meantime, chemical component of the solution is also tested and recorded in the progress of freezing-thawing cycling. Then, the nuclear magnetic resonance (NMR) test and magnetic resonance images (MRI) test on samples are conducted with the help of the AniMR-150 NMR imaging system. After a series of tests, the sample's appearance, dry mass, porosity, T2 spectrum, solution's pH, solution's metallic ion concentration, and magnetic resonance images are obtained and analyzed. The results show that dry mass loss and porosity grow with F-T cycles increase and pH value decrease. Montmorillonite, illite, and clay in sandstone react with sulfuric acid solution; as a consequence, K +, Mg 2+, Fe 3+, and Al 3+ separate out, and the solution's pH and concentration of K +, Mg 2+, Fe 3+, and Al 3+ increase with F-T cycles. Acid erosion and F-T cycling lead to the generation of new micropores and expansion of micropores at the beginning; when the acid solution is exhausted, new micropores generate under the effect of freezing-thawing cycling, and micropores in samples keep developing and expanding with the increase of freezing-thawing cycles. Coupled effect of acid corrosion and recurrent freezing-thawing cycling causes much more serious deterioration to sandstone samples than acid corrosion.